2006
DOI: 10.1128/aem.72.2.1639-1644.2006
|View full text |Cite|
|
Sign up to set email alerts
|

Enhanced Benzaldehyde Tolerance in Zymomonas mobilis Biofilms and the Potential of Biofilm Applications in Fine-Chemical Production

Abstract: Biotransformation plays an increasingly important role in the industrial production of fine chemicals due to its high product specificity and low energy requirement. One challenge in biotransformation is the toxicity of substrates and/or products to biocatalytic microorganisms and enzymes. Biofilms are known for their enhanced tolerance of hostile environments compared to planktonic free-living cells. Zymomonas mobilis was used in this study as a model organism to examine the potential of surface-associated bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(49 citation statements)
references
References 41 publications
2
47
0
Order By: Relevance
“…Recent studies showed that Z. mobilis biofilm cells exhibited a higher survival rate and metabolic activity than planktonic or free cells, which can also be developed and applied for the production of valuable bioproducts from toxic lignocellulosic hydrolysates (Li et al 2006;Todhanakasem et al 2014Todhanakasem et al , 2015Todhanakasem et al , 2018.…”
Section: Strategies To Enhance Inhibitor Tolerance Of Z Mobilismentioning
confidence: 99%
“…Recent studies showed that Z. mobilis biofilm cells exhibited a higher survival rate and metabolic activity than planktonic or free cells, which can also be developed and applied for the production of valuable bioproducts from toxic lignocellulosic hydrolysates (Li et al 2006;Todhanakasem et al 2014Todhanakasem et al , 2015Todhanakasem et al , 2018.…”
Section: Strategies To Enhance Inhibitor Tolerance Of Z Mobilismentioning
confidence: 99%
“…than their planktonic or freely swimming counterparts (7,9,16,19,29,40). There has been growing interest in recent years in the exploitation of these robust catalysts for biotechnological applications (e.g., biotransformations) to produce value-added chemicals (10,11,12,27). These studies have shown that the use of biofilms may overcome major bottlenecks in classical biocatalysis processes, such as substrate/product toxicity and short-term biocatalytic stability.…”
mentioning
confidence: 99%
“…Current research with biofilms has begun to focus on the production of high-priced chemicals (Gross et al, 2007;Li et al, 2006;Setyawati et al, 2009).…”
Section: Introductionmentioning
confidence: 99%